When applied early propranolol is more effective. - Milano, A. (European Journal of Pediatric Dermatology, 2012)
A 45-day-old baby was first observed due to the presence of 3 x 2 cm hemangioma on the abdomen with predominant superficial component (Fig. 1). We offered to the parents a treatment with 1% topical propranolol twice per day and explained the usefulness to apply it initially only on one half of hemangioma, in this case the right half, in order to verify the effectiveness of the drug. After one month we reviewed the child and we saw to close examination that the right half was less infiltrated, had more evident gray areas and less marked satellites (Fig. 2). From that moment propranolol was applied on the entire hemangioma. We observed again the child after 3 months and we noticed surprisingly that the improvement was still much more evident on the right half of hemangioma (Fig. 3), despite propranolol had been applied on the entire hemangioma for 3 months.